(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
Rabindranath Tagore’s Chokher Bali and D.H Lawrence’s Sons and Lovers are two famous novels in the early 20th century from two different social culture. Both these novels have particular important issues in them to be discussed. As in Chokher Bali we find Tagore has presented his idea in feminism, man-woman relationship, woeful condition of widow in his contemporary society etc. In the same way in Sons and Lovers Lawrence has talked about critical mother-son relationship, social bondage among the characters, description of nature, problems in the lives of working class etc. Though Chokher Bali and Sons and Lovers are from different social context but they can be compared through the commonly discussed issue in them that is complex mother-son relationship and the impact of motherhood to the sons. This paper is going to discuss the impact of excessive motherly affection to the life of son, similarities and dissimilarities in mother-son relationship in Chokher Bali and Sons and Lovers.